Total hip arthroplasty in the setting of tuberculosis infection of the hip: a systematic analysis of the current evidence. (4th May 2019) - Sultan, Assem A.; Dalton, Sarah E.; Umpierrez, Erica; Samuel, Linsen T.; Rose, Emily; Tamer, Pierre; Rabin, Jacob M.; Mont, Michael A.
ABSTRACT: Introduction : Total hip arthroplasty (THA) is a viable option to restore mobility and relieve pain in patients with severe post-tuberculous arthritis, but has been controversial due to concerns of disease reactivation. Over the past several decades, a number of authors have reported outcomes of THA for tuberculosis (TB) infections. However, there is marked heterogeneity in regard to disease activity, surgical approaches, and the use of chemoprophylaxis in these studies. Areas covered : The purpose of this review was to critically assess: 1) patient characteristics; 2) perioperative planning; 3) clinical outcomes; 4) radiographic outcomes; and 5) complications of THA in the setting of tuberculosis of the hip. Expert opinion : THA is an effective treatment for post-TB hip arthritis. There has been controversy regarding its safety during the past several decades, as it has been thought to increase the risk of disease reactivation. While studies thus far have shown generally favorable results, they have been limited by small sample sizes and their design as retrospective case series. Comparison of these studies reveals marked heterogeneity in the clinical management of this complex disease. However, synthesis of their findings demonstrates favorable outcomes and low rates of complication, including disease reactivation particularly when perioperative anti-tuberculosis therapy is instituted.